MANAGING ENVIRONMENTAL AND ECONOMIC PERFORMANCE: A REVIEW OF THEORY AND PRACTICE ON PERFORMANCE MEASUREMENT - Tsu Way, Stephanie Phang; Nabiha, A.K. Siti; Jalaludin, Dayana (The International Journal of Accounting and Business Society, 2014)
As businesses struggle to maintain sustainability, a great deal of interest has focused on the issues of performance measurement systems. This paper provides a literature review on the evolution of performance measurement systems, from the traditional performance measures to the sustainable balanced scorecard. More importantly, this paper highlights the vital role of sustainable balanced scorecard as a tool that manages both economic and environmental performance. Majority of the existing sustainable balanced scorecard studies were found to be of normative nature giving limited information on how the integration process between economic and environmental dimensions is being carried out via balanced scorecard. Future research is needed to enhance the understanding of the role of the sustainable balanced scorecard as an important tool in the management of economic and environmental performance in the organization.Keywords:Â  Balanced Scorecard, Environmental management, Sustainability, Eco-efficiency